Factors Influencing Formative Assessment Practices of Junior High School Social Studies Teachers - Eshun, Isaac; Ochour, Benjamin Kwabena; Bordoh, Anthony (Innovare Journal of Education, 2024)
The study investigated factors that influence formative assessment practices of Social Studies in the Techiman Municipality of the Bono East Region of Ghana. A quantitative approach with a descriptive survey research design was employed for the study. For the target population, all eighty-four public junior high school (JHS) Social Studies teachers in the Techiman Municipality of the Bono East Region of Ghana were chosen for the study. All the Social Studies teachers in the public JHSs in the Techiman Municipality were sampled for the study. The census sampling technique was employed to select the population for the study. Because the population was homogenous, all the Social Studies teachers, comprising ninety-five (95) teaching the subject at the JHS in the municipality, were selected for the study. The primary data collection instrument for the study was a twenty-two (22) five-point Likert itemized questionnaire used for the collection of data. Descriptive statistical tools were employed in analyzing the quantitative data. The quantitative figures were prearranged into frequency tables, simple percentages, weighted mean, and standard deviation for easy interpretation. The findings revealed that most teacher assessments are mainly influenced by external factors such as the nature and demand of the West Africa Examination Council’s (WAEC) questions and requirements set by the Municipal Director of Education or the school district. Therefore, the National Council for Curriculum and Assessment (NaCCA) should consider introducing interventions in teacher training universities and colleges that help improve classroom practices, including formative assessment practices.